2017
DOI: 10.21815/jde.017.018
|View full text |Cite
|
Sign up to set email alerts
|

Dental Group Practice and the Need for Dentists

Abstract: This study compared the number of patients treated per year by general dentists and dental hygienists in solo practice and by those employed by a large group practice. Information on the annual number of patient visits to solo general dental practitioners comes from the 2013 American Dental Association (ADA) Survey of Dental Practice. Patient visits were divided by 2.5 to estimate the number of patients treated annually. The data on group practices come from HealthPartners (HP) of Minnesota, a large not-for-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…In part, this results from some schools’ closing their Advanced Education in General Dentistry or General Practice Residency programs. However, the demand for postdoctoral general dentistry programs may expand in the future as owners of group practices prefer to hire graduates who have completed that type of training 22 , 23 …”
Section: Areas Of Challengementioning
confidence: 99%
“…In part, this results from some schools’ closing their Advanced Education in General Dentistry or General Practice Residency programs. However, the demand for postdoctoral general dentistry programs may expand in the future as owners of group practices prefer to hire graduates who have completed that type of training 22 , 23 …”
Section: Areas Of Challengementioning
confidence: 99%
“…Increasingly, dental providers in the United States are employed in large dental group practices with 500 or more employees [ 1 – 3 ]. These care delivery systems, along with Federally Qualified Health Care Centers, have become part of the safety net for low-income enrolled children and pregnant women whose healthcare is paid for largely by the national and state governments [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 These estimates vary because of differences in estimation methods. 10 Whatever the actual number of patients treated annually per dentist, a 2015 American Dental Association (ADA) survey reported that close to 40% of solo practice dentist owners said they were not as busy as they would like to be. The higher estimate comes from selfreporting.…”
Section: Current Supply Of Dentists and Population Demandmentioning
confidence: 99%
“…The former number was seen after the 2007 to 2009 recession. 10 Whatever the actual number of patients treated annually per dentist, a 2015 American Dental Association (ADA) survey reported that close to 40% of solo practice dentist owners said they were not as busy as they would like to be. 11 Thus, many dentists indicated that they already can manage more patients than they are currently treating.…”
Section: Current Supply Of Dentists and Population Demandmentioning
confidence: 99%
See 1 more Smart Citation